2020
DOI: 10.1016/j.ijid.2020.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Building resilient and responsive research collaborations to tackle antimicrobial resistance—Lessons learnt from India, South Africa, and UK

Abstract: Research, collaboration, and knowledge exchange are critical to global efforts to tackle antimicrobial resistance (AMR). Different healthcare economies are faced with different challenges in implementing effective strategies to address AMR. Building effective capacity for research to inform AMR-related strategies and policies is recognised as an important contributor to success. Interdisciplinary, intersector, as well as international collaborations are needed to span global to local efforts to tackle AMR. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The present results and previous studies demonstrated that the fight against AMR in community pharmacies might play within the limits of environmental work contexts to support ASU [ 25 , 58 , 59 , 60 , 61 ]. The concern for most community pharmacists was the lack of available materials, resources, surveillance systems, and infrastructure-supported collaboration with other healthcare providers for providing AMR practice [ 62 ]. Some mentioned they need a national guideline of antibiotic treatment in community pharmacies with availability and that is up to date.…”
Section: Discussionmentioning
confidence: 99%
“…The present results and previous studies demonstrated that the fight against AMR in community pharmacies might play within the limits of environmental work contexts to support ASU [ 25 , 58 , 59 , 60 , 61 ]. The concern for most community pharmacists was the lack of available materials, resources, surveillance systems, and infrastructure-supported collaboration with other healthcare providers for providing AMR practice [ 62 ]. Some mentioned they need a national guideline of antibiotic treatment in community pharmacies with availability and that is up to date.…”
Section: Discussionmentioning
confidence: 99%
“…When developing AMS programmes for surgical teams, the proposed framework can be applied to ensure that the key components necessary for sustainable change are addressed. This framework builds on research from high-, lowand middle-income countries [9,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…123 These newly created infrastructures and platforms provide excellent research opportunities to study and tackle other infectious diseases including drug-resistant pathogens. 124,125 On the societal level, awareness and sensitization regarding infectious diseases and IPC has been boosted by the COVID-19 pandemic. 124 This awareness could reinforce the role of these disciplines within hospitals and healthcare systems, increase chances for research funding, and facilitate support from public health authorities.…”
Section: Net Effect On Amr In 2020mentioning
confidence: 99%